Endovascular Management of Acute Pulmonary Embolism Using the Ultrasound-Enhanced EkoSonic System - Garcia, Mark J. (Seminars in Interventional Radiology, 2015)
Acute, symptomatic pulmonary embolism (PE) in the massive and submassive categories continues to be a healthcare concern with significant risk for increased morbidity and mortality. Despite increased awareness and venous thromboembolism prophylaxis, endovascular treatment is still an important option for many of these patients. There are a variety of techniques and devices used for treating PE, but none have been evaluated as extensively as the EkoSonic endovascular system that is also currently the only FDA-approved device for the treatment of pulmonary embolism. This article describes the use of the EkoSonic device for this patient population.
Keywords: pulmonary embolism; ultrasound-enhanced thrombolysis; EKOS; endovascular treatment; interventional radiology